The Matlab environment as a learning tool for teaching future engineers in transient processes in electrical systems - Lazarev , N.; Rudevich , N. (Problems of Engineer-Pedagogical Education, 2023)
The possibilities and features of using the SimPowerSystems expansion pack of the Matlab program as a learning tool for teaching future engineers in transient processes in electrical systems are discussed in the article. It was found that the SimPowerSystems pack allows to create virtual models of electrical systems for studying transient processes with symmetric and asymmetric short circuits. In addition, it can be used for determining the dependencies between the symmetrical components of voltages and currents with longitudinal and transverse asymmetry. At the same time, it allows to study the distribution of symmetrical components of currents and voltages during asymmetric short circuits. It can also be used for analysing static and dynamic stability and measures to preserve it. A generalized methodology has been developed for using the Simulink and SimPowerSystems Matlab expansion packs as a learning tool for studying transient processes in an electrical system, which involves the certain sequence of actions. Firstly, it creating a model file, placing and connecting blocks in the model window. Secondly, changing model parameters and setting simulation parameters. Thirdly, performing modelling, observing and registering processes in the model, as well as saving the model. It is proved that the use of the Matlab environment as a learning tool will contribute to the formation of students not only professional knowledge, skills but also motivational-targeted, cognitive, emotional-volitional and communicative professionally important qualities. It is concluded that the Matlab environment is useful as a learning tool for the following disciplines: “Theory of Automatic Control”, “Electric Machinery”, “Basic Physical Processes in Electric Power Systems”, “Electromagnetic Transient Processes”, “Electromechanical Transient Processes”, “Electrical Systems and Networks” , “Electrical Part of Stations and Substations” and “Simulation of Electric Power and Electromechanical Systems and Devices”. It is recommended to use the Matlab environment as a learning tool in the process of training by the following specializations: power stations, electrical systems and networks, management systems of production and distribution of electricity, cybersecurity technology in the power sector, energy management and energy-efficient technology.